Sharing experiences in conducting small group discussions in medical education - Ismawi, Hidayatul Radziah; Al-Ani, Ali Sabri Radeef; Mat Harun, Noraihan; Ahmad Basri, Nadzirah; Abd Rahman, Mohd Aizuddin (Malaysian Integrated Medical Professionals Association, 2021)
This e-book was published to embrace the concept of open access of knowledge and sustainability. Small group discussion is a process of conducting a purposeful organised interactive session to critically discuss a specific topic, resolve a particular issue or complete a designated group task. This book aims to share the authors' experiences with small group discussions as medical lecturers.